2015
DOI: 10.1103/physrevd.92.044046
|View full text |Cite
|
Sign up to set email alerts
|

Stability bounds on compact astrophysical objects from information-entropic measure

Abstract: We obtain bounds on the stability of various self-gravitating astrophysical objects using a new measure of shape complexity known as configurational entropy. We apply the method to Newtonian polytropes, neutron stars with an Oppenheimer-Volkoff equation of state, and to self-gravitating configurations of complex scalar field (boson stars) with different self-couplings, showing that the critical stability region of these stellar configurations obtained from traditional perturbation methods correlates well with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(100 citation statements)
references
References 29 publications
2
98
0
Order By: Relevance
“…We also added a longevity study of two-dimensional oscillons, since these too have yet to be shown to decay in numerical simulations. Motivated by these results, in the present work we extend our studies of the longevity of resonant and 2d oscillons using a recently proposed measure of spatial complexity known as Configurational Entropy (CE) [32], which has been applied to many physical systems, from solitons in field theories [33][34][35][36][37][38] to phase transitions [39][40][41], and to astrophysics and cosmology [42][43][44][45][46].…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…We also added a longevity study of two-dimensional oscillons, since these too have yet to be shown to decay in numerical simulations. Motivated by these results, in the present work we extend our studies of the longevity of resonant and 2d oscillons using a recently proposed measure of spatial complexity known as Configurational Entropy (CE) [32], which has been applied to many physical systems, from solitons in field theories [33][34][35][36][37][38] to phase transitions [39][40][41], and to astrophysics and cosmology [42][43][44][45][46].…”
Section: Figmentioning
confidence: 99%
“…Following this stability trend, CE was used to determine the Chandrasekhar limit for white dwarfs to few percent accuracy [42]. For generalrelativistic neutron and boson stars, the critical points of CE nearly paralleled their critical stability regions determined by perturbation theory [43]. Additionally, CE has been employed as a predictor of stability in the study of decay rates in hydrogen [47].…”
Section: Figmentioning
confidence: 99%
“…[2,3] for studying the stability of mesons and scalar glueballs. The nuclear configurational entropy is based upon the information entropy, implemented by the recently introduced configurational entropy [6][7][8][9], for spatially-localized physical systems. As the the cross section of any nuclear reaction is spatially-localized and employed to characterize the probability that any reaction occurs, the analysis of the shape complexity of classical field configurations can be implemented in the context of cross sections.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16], emulating the Shannon's information entropy, was also studied in Refs. [17][18][19][20]. In addition, it was used in order to predict the relative stability of physical configurations in Refs.…”
Section: Introductionmentioning
confidence: 99%